Peningkatan Ekonomi Desa melalui Pemberdayaan Masyarakat dalam Pengolahan Limbah Menjadi Pupuk Organik - Fauzan, Slamet; Nugroho, Purbo; Agustina, Shinta; Moliani, Ayuneng Indah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Samar Village was located in Pagerwojo District, Tulungagung Regency. The majority of residents in Samar Village focus in the livestock sector. The average cow waste produced 20 – 30 kg in one day. Handling of livestock waste needs to be done immediately so that waste accumulation does not have a negative impact on the surrounding environment. The problem is, the community does not have expert knowledge in processing the livestock waste produced. If left unchecked, it will cause a continuous and mounting buildup of livestock waste. Based on the problems faced by partners, the community service team collaborates with the village government to try to educate and empower the community in processing livestock waste into manure with high economic value. The method of implementing manure start from planning, implementing and evaluating the program which includes practical activities for making manure, testing the effectiveness of fertilizer and socializing the packaging and marketing of the products produced. This program also utilizes appropriate technology, namely a sieving machine that was recently handed over from the State University of Malang Service to Samar Village. Making this fertilizer requires a fermentation process mixed with an activator (EM4) and molasses (cane molasses) mixed evenly. In the process of making the fertilizer, it is closed tightly so that it is not exposed to air from outside and reopened within ± 2 weeks. The results of the effectiveness test by comparing plants given manure were proven to have benefits in increasing plant growth. This community empowerment program was successful because of the high enthusiasm of the community in efforts to increase community income and overcome the problem of livestock waste.